Eucharist and presence - O'Loughlin, Frank (The Australasian Catholic record, 2025)
There are pastoral problems which cannot be addressed without bringing a theological perspective to bear on them. Every aspect of the Christian faith is understood within the limited capacities of human thinking, and human thinking changes as history moves on. If some aspects of the faith are tied up with particular ways of understanding which are no longer effective pastorally or theologically, then change is required. When we acknowledge that every understanding of the Christian faith has roots in its particular time, place and culture, then a sensitivity to changes taking place in those contexts requires a reconsideration of the way the continuing faith is to be expressed in that new situation.